Composition for forming anode of lithium secondary battery

By using a binder containing a triblock copolymer, the problem of insufficient mechanical properties of the anode of the lithium secondary battery is solved, high mechanical properties and electrochemical stability are achieved, and manufacturing costs are reduced.

CN119495708APending Publication Date: 2025-02-21HYUNDAI MOTOR CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311703710.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-14
Filing Date
2023-12-12
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the manufacturing cost of lithium secondary batteries, especially in improving the mechanical properties of the anode.

Method used

A binder containing a triblock copolymer, which has soft and hard blocks, is employed to form excellent mechanical properties including moldability, electrochemical stability and tensile strength.

Benefits of technology

The high mechanical properties and electrochemical stability of the lithium secondary battery anode are achieved, reducing manufacturing costs and improving the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495708A_ABST
    Figure CN119495708A_ABST
Patent Text Reader

Abstract

The present invention particularly discloses a composition for forming an anode of a lithium secondary battery, comprising an anode active material, a conductive material, and a binder. Specifically, the binder comprises a triblock copolymer, and the triblock copolymer is provided with a soft block, a first hard block and a second hard block; the soft block is derived from an aliphatic or alicyclic diene monomer and forms a rubber phase at room temperature; the first hard block and the second hard block are respectively connected to two tail ends of the soft block, are derived from an aromatic ring-containing ethylenic bond type unsaturated monomer and form a glass phase at room temperature; wherein the binder contains particles having an average diameter (D50) of 1 [mu] m or more and 50 [mu] m or less.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to Korean Patent Application No. 10-2023-0106486, filed on Aug. 14, 2023, which is hereby incorporated herein by this reference in its entirety for all purposes. Technical Field

[0003] The present invention relates to a composition for forming an anode of a lithium secondary battery, the composition comprising a binder containing a triblock copolymer having a soft block and a hard block. Background Art

[0004] Lithium secondary batteries have been widely used in the portable electronic device market since they were first commercialized in the 1990s and continue to receive attention as the most studied energy storage system. Due to their characteristics, such as high driving voltage, high energy density, low self-discharge rate, high-speed performance, and long cycle stability, lithium secondary batteries meet the appropriate requirements as an energy source for electric vehicles.

[0005] However, lithium secondary batteries used in electric vehicles face three major problems: safety, operating time, and cost. The safety and operating time issues can be solved by all-solid-state batteries, but cost is a factor that hinders the widespread application of lithium secondary batteries, so a lot of research has been conducted to save the cost of lithium secondary batteries.

[0006] Reducing the energy consumption required to manufacture lithium secondary batteries or increasing the thickness of their electrodes is one of the most effective ways to save the manufacturing cost of lithium secondary batteries. In the conventional technology of manufacturing electrodes, the electrodes are formed by pouring a slurry obtained by mixing an electrode active material, a polymer binder and a conductive additive in water or an organic solvent onto a collector, drying and pressing the slurry. However, since the energy required to prepare the slurry and apply it to the collector in this way accounts for about 50% of the energy consumed by the entire manufacturing process, in order to save the manufacturing cost of lithium secondary batteries, a process for manufacturing electrodes by a dry method without using a solvent has been studied.

[0007] Although much research has been conducted on techniques for manufacturing electrodes by a dry process, research and development of techniques for manufacturing an anode having excellent mechanical properties such as formability, electrochemical stability, and tensile strength by a dry process and a composition for forming the anode are still needed. Summary of the invention

[0008] In a preferred aspect, the present invention provides a composition for forming a lithium secondary battery anode. The composition comprises a binder containing a triblock copolymer, and the triblock copolymer has a hard block that contributes to excellent mechanical properties and a soft block with flexibility. Such a composition is not only easy to shape and stable under negative potential, but also can be firmly combined with anode active materials. In addition, it has excellent tensile strength and forms a three-dimensional network, which can be firmly combined with anode active materials and conductive materials.

[0009] In some aspects, the lithium secondary battery is an all-solid-state battery. The term "all-solid-state battery" as used herein refers to a rechargeable secondary battery comprising a solid electrolyte (e.g., gel or polymer (cured)), which may include ionomers and other electrolyte components for transferring ions between the electrodes of the battery.

[0010] On the one hand, a composition for forming an anode of a lithium secondary battery is provided, the composition comprising an anode active material, a conductive material and a binder. The binder comprises a triblock copolymer, the triblock copolymer having a soft block, a first hard block and a second hard block, the soft block being derived from an aliphatic or alicyclic diene monomer and forming a rubber phase at room temperature, the first hard block and the second hard block being connected to the two ends of the soft block, respectively, being derived from an aromatic ring-containing ethylenically unsaturated monomer and forming a glass phase at room temperature, and wherein the binder comprises an average diameter (D 50 ) are particles of about 1 μm or more and 50 μm or less.

[0011] As referred to herein, the rubber phase or rubber state is above the Tg (glass transition temperature) of the material, i.e., at this time the material can be in a more rubbery state and relatively soft and pliable. Thus, when the material described herein forms a rubber phase at room temperature (e.g., 25° C.), the material can be above its glass transition temperature at room temperature (25° C.) and can be in a relatively rubbery state or more pliable state.

[0012] As referred to herein, a glass phase or glassy state is below the Tg (glass transition temperature) of a material, and at this point the material may be in a more rigid or glass-like configuration. Thus, when a material described herein forms a glass phase at room temperature (e.g., 25° C.), the material may be below its glass transition temperature at room temperature (25° C.) and may be in a relatively rigid or hardened state.

[0013] In some embodiments, the binder is spherical and has an average sphericity of about 0.7 or greater and about 1.0 or less.

[0014] In some embodiments, the first and second glass transition temperatures corresponding to the first and second hard blocks, respectively, are about 50°C or higher and about 120°C or lower, and the third glass transition temperature corresponding to the soft block is about -120°C or higher and about -50°C or lower.

[0015] In some embodiments, the soft block is derived from an aliphatic diene-based monomer containing one or more selected from butadiene-based monomers, pentadiene-based monomers, and hexadiene-based monomers.

[0016] In some embodiments, the butadiene-based monomer includes one or more selected from 1,2-butadiene, 1,3-butadiene, isoprene, and chloroprene.

[0017] In some embodiments, the first hard block and the second hard block are each independently derived from an aromatic ring-containing ethylenically unsaturated monomer containing one or more of a styrene-based monomer and an aromatic (meth)acryloyl-based monomer.

[0018] In some embodiments, the styrene-based monomer includes one or more selected from styrene, α-methylstyrene, p-methylstyrene, p-methoxystyrene, p-ethoxystyrene, tert-butoxystyrene, p-acetoxystyrene, p-chlorostyrene, p-bromostyrene, 2,4-dimethylstyrene, 3,5-dimethylstyrene, and 2,4,6-trimethylstyrene.

[0019] In some embodiments, the aromatic (meth)acryloyl monomer includes one or more selected from the group consisting of benzyl acrylate, benzyl methacrylate, phenoxy acrylate, phenoxy methacrylate, phenyl acrylate, phenyl methacrylate, phenethyl acrylate, and phenethyl methacrylate.

[0020] In some embodiments, the anode active material includes one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing active material.

[0021] In some embodiments, the conductive material includes one or more selected from graphite, activated carbon, carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, and carbon fibers.

[0022] In some embodiments, the composition includes a total amount of about 10 wt % to 60 wt % of the first hard block and the second hard block, based on the total weight of the triblock copolymer.

[0023] In some embodiments, the first hard block and the second hard block each have a weight average molecular weight of about 9,000 g / mol or greater and about 20,000 g / mol or less.

[0024] In some embodiments, the composition comprises the binder in an amount of about 3 to 15 weight percent, based on the total weight of the composition.

[0025] In one aspect, an anode of a lithium secondary battery comprising the composition described herein is provided.

[0026] In one aspect, there is provided a lithium secondary battery comprising an anode as described herein.

[0027] In one aspect, a vehicle is provided that includes a lithium secondary battery as described herein.

[0028] By using the composition for forming a lithium secondary battery anode according to various exemplary embodiments of the present invention, it is possible to manufacture not only a self-supporting film for a lithium secondary battery anode that is electrochemically stable at a negative potential due to strong interaction with an anode active material or a conductive material, has excellent tensile strength, and is easy to form, but also an anode for a lithium secondary battery and a lithium secondary battery containing the self-supporting film.

[0029] Other aspects of the invention are disclosed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 An exemplary internal structure of a binder included in a self-standing film for a lithium secondary battery anode according to an exemplary embodiment of the present invention is shown.

[0031] Figure 2 An exemplary method of manufacturing an exemplary anode using an exemplary composition for forming an anode of a lithium secondary battery according to an exemplary embodiment of the present invention is shown.

[0032] Figure 3A An SEM image of SBS particles applied to the composition for forming an anode according to Example 1 is shown.

[0033] Figure 3B An SEM image of SBS particles applied to the composition for forming an anode according to Comparative Example 1 is shown.

[0034] Figure 3C is a graph showing the results of particle size analysis of SBS particles applied to the composition for forming an anode according to Example 1.

[0035] Figure 4A : is an image showing the result of visually observing the surface of the electrode manufactured using the composition for forming an anode according to Example 4.

[0036] Figure 4B : is an image showing the result of visually observing the surface of the electrode manufactured using the composition for forming an anode according to Example 6. DETAILED DESCRIPTION

[0037] Hereinafter, a composition for forming an anode of a lithium secondary battery will be described in detail so that a person having ordinary knowledge in the technical field to which the present invention pertains can easily practice the present invention.

[0038] The above purpose, other purposes, features and advantages of the present invention will be easily understood by the following preferred embodiments related to the accompanying drawings. However, the present invention is not limited to the embodiments described herein and can be implemented in other forms. The embodiments described herein are provided so that the disclosed content can become complete and sufficient, and the spirit of the present invention can be fully conveyed to those skilled in the art. In all the accompanying drawings, similar elements are represented by similar reference numerals. In the accompanying drawings, for the sake of clarity of the present invention, the size of the structure is larger than the actual size. The terms "first", "second" etc. used in the specification can be used to describe various components, but the components should not be interpreted as being limited to these terms. These terms are only used to distinguish one component from another component. For example, without departing from the scope of the present invention, the first component can be referred to as the second component, and the second component can also be referred to as the first component. As used in this article, unless the context clearly indicates otherwise, the singular form "one", "one" and "the / said" are intended to also include plural forms. It should also be understood that when used in this specification, the terms "comprise", "include" or "have" specify the presence of the features, regions, wholes, steps, operations, elements and / or components described, but do not exclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components and / or combinations thereof. It should also be understood that when an element such as a layer, film, region or sheet is referred to as being "above" another element, it can be directly above the other element, or there can be intermediate elements between them. Similarly, when an element such as a layer, film, region or sheet is referred to as being "below" another element, it can be directly below the other element, or there can be intermediate elements between them. Unless otherwise stated, all numbers, values ​​and / or expressions used in this article to represent the amount of components, reaction conditions, polymer compositions and mixtures should be considered as approximate values ​​containing various uncertainties (especially inherently existing when obtaining these values, which will affect the measured values), and are therefore understood to be modified by the term "about" in all cases. Unless otherwise stated or apparent from the context, the term "about" as used herein is understood to be within the normal tolerance range in the art, such as within two standard deviations of the mean. "About" may be understood to be within 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05%, or 0.01% of the stated value. Unless the context clearly indicates otherwise, all numerical values ​​provided herein are modified by the term "about".

[0039] In addition, when a numerical range is disclosed in this specification, the range is continuous and includes all values ​​from the minimum value of the range to its maximum value, unless otherwise specified. In addition, when such a range involves integer values, all integers including the minimum value to the maximum value are included unless otherwise specified. For example, the range "5 to 10" will be understood to include any sub-ranges (e.g., 6 to 10, 7 to 10, 6 to 9, 7 to 9, etc.) and individual values ​​of 5, 6, 7, 8, 9 and 10, and will also be understood to include any value between the valid integers in the range, such as 5.5, 6.5, 7.5, 5.5 to 8.5, 6.5 to 9, etc. In addition, for example, the range "10% to 30%" will be understood to include sub-ranges (e.g., 10% to 15%, 12% to 18%, 20% to 30%, etc.) and all integers (including values ​​of 10%, 11%, 12%, 13%, etc. up to 30%), and will also be understood to include any values ​​between the valid integers in the stated range, e.g., 10.5%, 15.5%, 25.5%, etc.

[0040] It should be understood that the term "vehicle" or "vehicle-like" or other similar terms as used herein generally include motor vehicles, such as passenger vehicles including sport utility vehicles (SUVs), buses, trucks, various commercial vehicles, watercraft including various boats and ships, aircraft, etc., and include hybrid vehicles, electric vehicles, plug-in hybrid electric vehicles, hydrogen-powered vehicles, and other alternative fuel vehicles (e.g., fuels derived from non-petroleum energy sources). As mentioned herein, a hybrid vehicle is a vehicle with two or more power sources, such as a vehicle that has both gasoline power and electric power. In certain preferred aspects, the vehicle can be electric, including a hybrid vehicle, a plug-in hybrid vehicle, or a vehicle with electricity as the primary or sole power source.

[0041] According to an embodiment of the present invention, a composition for forming an anode of a lithium secondary battery comprises an anode active material, a conductive material and a binder. The binder comprises a triblock copolymer having a soft block, a first hard block and a second hard block, wherein the soft block is derived from an aliphatic or alicyclic diene monomer and forms a rubber phase at room temperature, wherein the first hard block and the second hard block are respectively connected to the two ends of the soft block, and are derived from an aromatic ring-containing ethylenically unsaturated monomer and form a glass phase at room temperature, wherein the binder comprises an average diameter (D 50 ) are particles of 1 μm or more and 50 μm or less.

[0042] The average diameter of the binder (D 50 ) refers to the diameter corresponding to 50% of the cumulative volume distribution measured by a laser diffraction / scattering particle size distribution measuring device.

[0043] The soft block may include repeating units derived from an aliphatic diene monomer and / or an alicyclic diene monomer and exhibit a rubber phase at room temperature. Specifically, the soft block may be derived from an aliphatic diene monomer including at least one selected from a butadiene monomer, a pentadiene monomer, and a hexadiene monomer.

[0044] The butadiene-based monomer may include one or more selected from the group consisting of 1,2-butadiene, 1,3-butadiene, isoprene, and chloroprene.

[0045] The pentadienyl monomers may include 1,2-pentadiene, 1,3-pentadiene, 1,4-pentadiene, 2,3-pentadiene, 2-methyl-1,3-pentadiene, 2-methyl-1,4-pentadiene, 2-methyl-2,3-pentadiene, 2-methyl-2,4-pentadiene, 3-methyl-1,3-pentadiene, 3-methyl-1,4-pentadiene, 4-methyl-1,3-pentadiene, 2-ethyl-1,3-pentadiene, one or more of pentadiene, 2-ethyl-1,4-pentadiene, 2-ethyl-2,4-pentadiene, 3-ethyl-1,3-pentadiene, 3-ethyl-1,4-pentadiene, 4-ethyl-1,3-pentadiene, 1-chloro-1,3-pentadiene, 1-chloro-2,4-pentadiene, 2-chloro-1,3-pentadiene, 3-chloro-1,3-pentadiene, 3-chloro-1,4-pentadiene and 5-chloro-1,3-pentadiene.

[0046] The hexadiene-based monomers may include those selected from the group consisting of 1,2-hexadiene, 1,3-hexadiene, 1,4-hexadiene, 1,5-hexadiene, 2,3-hexadiene, 2,4-hexadiene, 2,5-hexadiene, 3,5-hexadiene, 2-methyl-1,3-hexadiene, 2-methyl-1,4-hexadiene, 2-methyl-1,5-hexadiene, 2-methyl-2,3-hexadiene, 2-methyl-2,4-hexadiene, 3-methyl-1,2-hexadiene, 3-methyl-1,3-hexadiene, 3-methyl-1,4-hexadiene, 3-methyl- At least one of 1,5-hexadiene, 3-methyl-2,4-hexadiene, 3-methyl-2,5-hexadiene, 4-methyl-1,3-hexadiene, 4-methyl-1,4-hexadiene, 4-methyl-2,3-hexadiene, 5-methyl-1,3-hexadiene, 5-methyl-1,4-hexadiene, 2-ethyl-1,3-hexadiene, 2-ethyl-1,4-hexadiene, 3-ethyl-1,2-hexadiene, 3-ethyl-1,3-hexadiene, 3-ethyl-1,4-hexadiene and 3-ethyl-1,5-hexadiene.

[0047] The triblock copolymers containing the soft block are characterized by excellent flexibility, extrudability and wear resistance.

[0048] The first and second hard blocks may include repeating units derived from an ethylenically unsaturated monomer having an aromatic ring and exhibit a glass phase at room temperature. Specifically, the aromatic ring included in the ethylenically unsaturated monomer may be a substituted or unsubstituted benzene ring or a substituted or unsubstituted naphthalene ring.

[0049] In addition, the aromatic ring may be connected to the main chain or the side chain of the repeating unit of the first hard block and the second hard block, and may be preferably connected to the side chain of the repeating unit of the first hard block and the second hard block.

[0050] The first hard block and the second hard block may each independently be derived from an aromatic ring-containing ethylenically unsaturated monomer having at least one of a styrene-based monomer and an aromatic (meth)acryloyl-based monomer.

[0051] The styrene-based monomer may include one or more selected from styrene, α-methylstyrene, p-methylstyrene, p-methoxystyrene, p-ethoxystyrene, tert-butoxystyrene, p-acetoxystyrene, p-chlorostyrene, p-bromostyrene, 2,4-dimethylstyrene, 3,5-dimethylstyrene, and 2,4,6-trimethylstyrene.

[0052] The aromatic (meth)acryloyl monomer may include one or more selected from the group consisting of benzyl acrylate, benzyl methacrylate, phenoxy acrylate, phenoxy methacrylate, phenyl acrylate, phenyl methacrylate, phenethyl acrylate, and phenethyl methacrylate.

[0053] Due to the aromatic ring structure contained in the repeating unit, the first hard block and the second hard block can be firmly bonded to the anode active material or the conductive material through π-π interaction. In addition, the first hard block and the second hard block form crosslinks through physical bonding with relatively low bonding energy, whereby, for example, below the glass transition temperature thereof, the shape and size of the blocks can be maintained, but above the glass transition temperature thereof, the blocks can be easily molded.

[0054] In addition, the first hard block and the second hard block can impart high strength properties to the triblock copolymer containing them.

[0055] Based on the total amount of the triblock copolymer, the total amount of the first hard block and the second hard block can be about 10 wt % to 60 wt %, preferably about 15 wt % to 55 wt %, and more preferably about 20 wt % to 50 wt %. When the amount of the first hard block and the second hard block meets the above numerical range, the bonding strength can be further improved due to the strong interaction with the anode active material or the conductive material, so that the triblock copolymer can have more excellent moldability due to appropriate flexibility.

[0056] The weight average molecular weight of each of the first hard block and the second hard block may be about 9,000 g / mol or more and about 20,000 g / mol or less, preferably about 9,500 g / mol or more and about 20,000 g / mol or less, more preferably about 10,000 g / mol or more and about 20,000 g / mol or less. When the weight average molecular weight of each of the first hard block and the second hard block satisfies the above numerical range, the physical crosslinking force between the binder and the anode active material or the conductive material can be improved to form a more stable three-dimensional network.

[0057] The first glass transition temperature and the second glass transition temperature corresponding to each of the first hard block and the second hard block may be about 50°C or higher and about 120°C or lower, and the third glass transition temperature corresponding to the soft block may be about -120°C or higher and -50°C or lower. Preferably, the first glass transition temperature and the second glass transition temperature are about 80°C or higher and 120°C or lower, and the third glass transition temperature is about -120°C or higher and about -80°C or lower. More preferably, the first glass transition temperature and the second glass transition temperature are about 80°C or higher and about 110°C or lower, and the third glass transition temperature is about -110°C or higher and about -80°C or lower. Therefore, when the first hard block, the second hard block and the soft block contained in the triblock copolymer have a glass transition temperature within the above numerical range, the composition containing the binder containing the triblock copolymer for forming the anode of a lithium secondary battery can be more reversibly molded. In addition, the durability and flexibility of the electrode manufactured from the composition are further improved, so that its shape can be more effectively maintained.

[0058] The soft block, the first hard block and the second hard block contained in the triblock copolymer can each realize independent performance without affecting each other. In other words, the soft block can provide flexibility, and the first hard block and the second hard block can provide a strong binding force with the anode active material for the self-supporting film of the anode of the lithium secondary battery finally formed. In addition, since the soft block and the hard block have different glass transition temperatures from each other, when the self-supporting film for the anode is formed (calendering, etc.) at a temperature higher than the hard block glass transition temperature, the formability of the triblock copolymer becomes easier. When the self-supporting film is immediately exposed to the corresponding temperature below the hard block glass transition temperature and above the soft block glass transition temperature after forming the film, the triblock copolymer has flexibility and maintains high strength, so that the self-supporting film for the anode of the lithium secondary battery thus obtained is not easy to break due to external stimuli.

[0059] The triblock copolymer is stable at a negative potential to suppress the occurrence of side reactions, and therefore, when the triblock copolymer is used as a binder for an anode of a lithium secondary battery, the life characteristics of the electrode can be improved.

[0060] The binder is substantially spherical and can be spherical or nearly spherical. Specifically, the binder can have an average sphericity of about 0.7 or greater and about 1.0 or less, preferably about 0.8 or greater and about 1.0 or less, more preferably about 0.9 or greater and about 1.0 or less. That is, before manufacturing the self-supporting film for the anode, the binder particles in the composition for forming the anode of the lithium secondary battery can be dispersed in the composition for forming the anode while remaining substantially spherical.

[0061] In this article, the sphericity of the binder is determined as follows: Measure the long diameter and short diameter of 10 randomly selected particles from the image of the binder particles observed using a scanning electron microscope (SEM), and calculate the ratio of the long diameter to the short diameter of each particle. The sphericity is the average value obtained from the ratio of the long diameter to the short diameter of 10 particles. The closer the sphericity is to 1, the closer it can be judged to be spherical.

[0062] The anode active material can include one or more selected from carbon-based active materials, silicon-based active materials, metal-based active materials capable of alloying with lithium, and lithium-containing active materials.

[0063] The carbon-based active material can be, for example, graphite, hard carbon, soft carbon, or graphene. The graphite can be artificial graphite, natural graphite, a mixture of artificial graphite and natural graphite, natural graphite coated with artificial graphite, or a combination thereof.

[0064] The silicon-based active material can be, for example, Si, SiO m , Si-C composite materials, Si-Q alloys, or combinations thereof, where 0 < m ≤ 2 and Q is an alkali metal, alkaline earth metal, element of Groups 13 to 16 of the periodic table, transition metal, rare earth element, or a combination thereof, provided that Q does not include Si.

[0065] The metal-based active material capable of alloying with lithium can include, for example, B, Al, Ga, In, Ge, Sn, Pb, P, As, Sb, Bi, Mg, Ca, Zn, Cd, Pd, Ag, Au, Pt, or their alloys, or their oxides.

[0066] The lithium-containing active material can be, for example, lithium-containing titanium composite oxide (LTO).

[0067] The conductive material can include at least one selected from graphite, activated carbon, carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, and carbon fiber.

[0068] The content of the binder can be about 3 wt % to 15 wt %, preferably about 6 wt % to 14 wt %, and more preferably about 10 wt % to 14 wt %, based on the total weight of the composition for forming the anode of a lithium secondary battery. When the amount of the binder satisfies the above numerical range, due to the strong interaction between the binder and the anode active material, a self-supporting film for the anode having excellent tensile strength and electrochemical stability even at a negative potential can be formed by the composition for forming the anode of a lithium secondary battery comprising the binder.

[0069] Film forming treatment can be performed to form a self-supporting film for the anode using a composition for forming a lithium secondary battery anode. The film forming treatment can be performed by a dry method. In other words, the composition for forming a lithium secondary battery anode used in the film forming treatment can be substantially free of solvent. In the case of a wet film forming treatment, since the slurry is in a liquid state, there is a limitation in increasing the load of the electrode, and there is a situation where a network structure between a binder and an active material / conductive material cannot be formed. However, since the film forming treatment according to the present invention is performed by a dry method, a lithium secondary battery with a high electrode load to achieve a high energy density can be manufactured, and a network structure can be formed more effectively between a binder and an active material.

[0070] The film forming process may include calendering (rolling). In other words, the anode active material layer can be formed by passing a composition for forming a lithium secondary battery anode containing an anode active material, a conductive material and a binder between a pair of rollers and pressing and rolling the composition. External forces such as shear force and tensile force are applied by such calendering, and a self-supporting film for a lithium secondary battery anode can be finally manufactured.

[0071] In addition, the triblock copolymer can form a three-dimensional network at the temperature and pressure of the film forming process. As described above, the active material domains or the conductive material domains and the binder are connected to each other to form a three-dimensional network, thereby making it possible to manufacture a lithium secondary battery anode with excellent tensile strength.

[0072] Example

[0073] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only intended to help understand the present invention, and are not intended to limit the scope of the present invention to these examples in any way.

[0074] <Example 1> Preparation of Composition 1 for Forming Anode

[0075] Graphite as an anode active material, carbon black as a conductive material, and SBS triblock copolymer in powder form (glass transition temperature of polystyrene block: 100° C., glass transition temperature of polybutadiene block: −100° C.) as a binder were mixed in a mass ratio of 96:1:3 without a solvent.

[0076] Herein, based on the total weight of the SBS triblock copolymer, the content of the polystyrene block is 40.5 wt %. The molecular weight of the SBS triblock copolymer is 57,000 g / mol, wherein the molecular weight of the polystyrene block is 11,500 g / mol, and the molecular weight of the polybutadiene block is 34,000 g / mol.

[0077] <Example 2> Preparation of Composition 2 for Forming Anode

[0078] A composition for forming an anode was prepared in the same manner as in Example 1, except that the mass ratio of graphite, conductive material, and binder was 95:1:4.

[0079] <Example 3> Preparation of Composition 3 for Forming Anode

[0080] A composition for forming an anode was prepared in the same manner as in Example 1, except that the mass ratio of graphite, conductive material, and binder was 94:1:5.

[0081] <Example 4> Preparation of Composition 4 for Forming Anode

[0082] A composition for forming an anode was prepared in the same manner as in Example 1, except that the mass ratio of graphite, conductive material, and binder was 93:1:6.

[0083] <Example 5> Preparation of Composition 5 for Forming Anode

[0084] A composition for forming an anode was prepared in the same manner as in Example 1, except that the mass ratio of graphite, conductive material, and binder was 87:1:12.

[0085] <Example 6> Preparation of Composition 6 for Forming Anode

[0086] Graphite as an anode active material, carbon black as a conductive material, and SBS triblock copolymer in powder form (glass transition temperature of polystyrene block: 100° C., glass transition temperature of polybutadiene block: −100° C.) as a binder were mixed in a mass ratio of 93:1:6 without a solvent.

[0087] Herein, based on the total weight of the SBS triblock copolymer, the content of the polystyrene block is 31 wt %. The molecular weight of the SBS triblock copolymer is 73,000 g / mol, wherein the molecular weight of the polystyrene block is 11,200 g / mol, and the molecular weight of the polybutadiene block is 51,000 g / mol.

[0088] <Comparative Example 1> Preparation of Composition 7 for Forming Anode

[0089] The composition for forming an anode was prepared in the same manner as in Example 1, except that pellet-form SBS (average diameter (D 50 ): 5mm) instead of SBS in powder form as a binder.

[0090] <Experimental Example 1> Observation of SBS particles

[0091] In order to observe the shape of the SBS particles, SEM images of the SBS particles applied to the compositions for forming an anode according to Example 1 and Comparative Example 1 were taken and are shown in FIG. Figure 3A and 3B middle. Figure 3A Shows the SEM image of SBS powder particles after becoming powder, Figure 3B Shown is a SEM image of SBS pellets before becoming powder.

[0092] like Figure 3A As shown, the SBS binder has a spherical particle shape even after being turned into powder.

[0093] Furthermore, the particle size of the SBS particles applied to the composition for forming an anode according to Example 1 was analyzed using a particle size analyzer (model name: SALD-2300, manufacturer: SHIMADZU), and as a result, it was found that the average diameter (D 50 ) is about 20 μm (see Figure 3C ). In addition, in the case of the SBS particles applied to the composition for forming an anode according to Comparative Example 1, it was confirmed that the average diameter (D 50 ) is about 0.5 cm. Therefore, it can be confirmed that the SBS particles according to Example 1 can form SBS particles of smaller size after being turned into powder.

[0094] <Comparative Example 2> Preparation of Composition 8 for Forming Anode

[0095] A composition for forming an anode was prepared in the same manner as in Example 1, except that PTTF was used as a binder instead of SBS.

[0096] <Experimental Example 2> Observation of whether a self-supporting film for anode is formed according to film forming temperature

[0097] In order to observe the effect of film forming temperature on the formation of a self-standing film for an anode, a film was formed by rolling the composition for forming an anode according to Example 4 using a double-roll press heated to a temperature of 120°C, and a film was formed by rolling the composition for forming an anode according to Example 4 using a double-roll press heated to a temperature of 80°C.

[0098] As a result, good film formation was observed at 120° C., but no film formation was observed at a temperature of 80° C. This means that film formation can be achieved at a temperature of 100° C. or higher, which is the glass transition temperature of polystyrene contained in the triblock copolymer.

[0099] <Experimental Example 3> Observation of the surface state of the self-supporting film for anode according to the polystyrene content

[0100] In order to observe the influence of the polystyrene content contained in the SBS triblock copolymer on the surface state of the self-standing film for anode, the anode forming compositions according to Examples 4 and 6 were subjected to film forming treatment by rolling using a twin roll press heated to 120°C.

[0101] As a result, filming was observed for the anode forming compositions according to Examples 4 and 6. However, in the case of Example 6 having a relatively low content of polystyrene blocks, the surface state of the self-standing film was inferior to that of the self-standing film formed from the anode forming composition of Example 4.

[0102] <Experimental Example 4> Measurement of tensile strength of self-supporting film for anode

[0103] First, a self-supporting film for an anode was manufactured by rolling the compositions for forming an anode according to Example 1 (content of SBS binder: 3 wt %), Example 4 (content of SBS binder: 6 wt %, content of SBS-based polystyrene block: 40.5 wt %), Example 6 (content of SBS binder: 6 wt %, content of SBS-based polystyrene block: 31 wt %) and Comparative Example 1 (content of PTFE binder: 3 wt %) under the following temperature conditions using a double-roll press.

[0104] Each manufactured self-supporting film for anode was punched out into 2 cm width and 6 cm length to prepare a sample of the self-supporting film, and the tensile strength was measured using a UTM device at a speed of 5 mm / min. The measurement results of the tensile strength are shown in Table 1 below.

[0105] Table 1

[0106] Composition Binder content Film forming temperature Tensile Strength Example 1 SBS 3 wt% 120℃ 0.728mPa Example 1 SBS 3 wt% 140℃ 0.556mPa Example 4 SBS 6 wt% 120℃ 1.281mPa Example 6 SBS 6 wt% 120℃ 0.874mPa Comparative Example 1 PTFE 3 wt% 120℃ 0.253mPa

[0107] As shown in Table 1, based on the same binder content, when the film-forming treatment is performed at a higher temperature, the tensile strength decreases. This is presumably because the higher the temperature at which the film-forming treatment is performed, the more stretching of the binder occurs, and when the temperature is lowered to room temperature after the film-forming treatment, the shrinkage rate of the binder becomes relatively large, resulting in the breaking of some three-dimensional network bonds inside the binder.

[0108] On the other hand, when the film forming process is carried out at the same temperature, the tensile strength when the binder content is 6 wt% is better than that when the binder content is 3 wt%, and the tensile strength when SBS is used as the binder is better than that when PTFE is used as the binder (Comparative Example 1).

[0109] The above results may be because the SBS binder forms a three-dimensional network connection between active materials, between conductive materials, or between active materials and conductive materials, thereby firmly bonding them.

[0110] In addition, even when the film-forming process is performed at the same temperature using the composition for forming an anode containing the same content of the SBS binder, the tensile strength of the self-supporting film for an anode manufactured is excellent in the case where the content of the polystyrene block in the SBS is high. In other words, as the content of the polystyrene block in the SBS binder increases, the mechanical properties of the self-supporting film for an anode manufactured from the composition containing the binder become excellent.

[0111] <Experimental Example 5> Observation of whether anodes are produced

[0112] The compositions for forming an anode according to Examples 1 to 6 were rolled by a double roll press under the temperature conditions shown in Table 2 below to produce self-supporting films. The self-supporting films were placed on one side of a copper foil (current collector) coated with a primer layer, respectively, and laminated by a laminating roll maintained at 120° C. to produce an anode for a lithium secondary battery.

[0113] Table 2 below shows the results of lamination under each condition, where O indicates a strong bond between the binder and the collector and no deformation of the self-supporting film for the anode, △ indicates that the self-supporting film was broken or separated from the collector when a strong pressure was applied, and X indicates a case where lamination itself was impossible.

[0114] Table 2

[0115]

[0116]

[0117] When the self-supporting film for anode formed at 120°C using the composition for forming an anode according to Examples 1 to 5 is laminated, as the content of the binder contained in the composition increases, the binder can be more firmly bonded to the collector. Specifically, when the content of the binder is as low as 3% by weight, the physical properties of the self-supporting film manufactured are poor, which also leads to poor physical properties of the anode manufactured after the lamination process, and when the binder content is 12% by weight, a strong anode can be formed by firmly bonding the self-supporting film for the anode to the copper foil. The above results may be because the higher the content of the SBS binder, the more three-dimensional network connections can be formed between the anode active materials, between the conductive materials, or between the active materials and the conductive materials.

[0118] Meanwhile, in order to observe whether the anode can be manufactured according to the content of the polystyrene block contained in the SBS binder, the compositions for forming the anode according to Examples 4 and 6 were subjected to film forming treatment at a temperature of 120° C. The laminated anodes are shown in FIG. Figure 4A and Figure 4B As a result, compared with the anode manufactured using the composition for forming an anode according to Example 4, the anode manufactured using the composition for forming an anode according to Example 6 had poor bonding between the binder and the current collector.

Claims

1. A composition for forming an anode for a lithium secondary battery, comprising: Anode active material, Conductive materials, and Binder, in, The binder comprises: A triblock copolymer, the triblock copolymer having a soft block, a first hard block and a second hard block, the soft block being derived from an aliphatic or alicyclic diene monomer and forming a rubber phase at room temperature, the first hard block and the second hard block being connected to two ends of the soft block, respectively, being derived from an aromatic ring-containing ethylenically unsaturated monomer and forming a glass phase at room temperature, wherein the binder comprises an average diameter D 50 Particles of 1 μm or more and 50 μm or less.

2. The composition for forming a lithium secondary battery anode according to claim 1, wherein The binder is spherical and has an average sphericity of 0.7 or more and 1.0 or less.

3. The composition for forming a lithium secondary battery anode according to claim 1, wherein: The first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively, are 50° C. or higher and 120° C. or lower, and the third glass transition temperature corresponding to the soft block is -120° C. or higher and -50° C. or lower.

4. The composition for forming a lithium secondary battery anode according to claim 1, wherein The soft block is derived from an aliphatic diene-based monomer including one or more selected from a butadiene-based monomer, a pentadiene-based monomer, and a hexadiene-based monomer.

5. The composition for forming a lithium secondary battery anode according to claim 4, wherein: The butadiene-based monomer includes one or more selected from 1,2-butadiene, 1,3-butadiene, isoprene and chloroprene.

6. The composition for forming a lithium secondary battery anode according to claim 1, wherein: The first hard block and the second hard block are each independently derived from an aromatic ring-containing ethylenically unsaturated monomer containing one or more of a styrene-based monomer and an aromatic (meth)acryloyl-based monomer.

7. The composition for forming a lithium secondary battery anode according to claim 6, wherein: The styrene-based monomer includes one or more selected from styrene, α-methylstyrene, p-methylstyrene, p-methoxystyrene, p-ethoxystyrene, tert-butoxystyrene, p-acetoxystyrene, p-chlorostyrene, p-bromostyrene, 2,4-dimethylstyrene, 3,5-dimethylstyrene and 2,4,6-trimethylstyrene.

8. The composition for forming a lithium secondary battery anode according to claim 6, wherein: The aromatic (meth)acryloyl monomer includes one or more selected from the group consisting of benzyl acrylate, benzyl methacrylate, phenoxy acrylate, phenoxy methacrylate, phenyl acrylate, phenyl methacrylate, phenethyl acrylate, and phenethyl methacrylate.

9. The composition for forming a lithium secondary battery anode according to claim 1, wherein: The anode active material includes one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing active material.

10. The composition for forming a lithium secondary battery anode according to claim 1, wherein: The conductive material comprises one or more selected from graphite, activated carbon, carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene and carbon fiber.

11. The composition for forming a lithium secondary battery anode according to claim 1, wherein: The composition includes a total amount of the first hard block and the second hard block of 10 wt % to 60 wt % based on the total weight of the triblock copolymer.

12. The composition for forming a lithium secondary battery anode according to claim 1, wherein: The first hard block and the second hard block each have a weight average molecular weight of 9,000 g / mol or more and 20,000 g / mol or less.

13. The composition for forming a lithium secondary battery anode according to claim 1, wherein: The composition includes the binder in an amount of 3 wt % to 15 wt % based on the total weight of the composition. 14 . An anode of a lithium secondary battery comprising the composition for forming an anode of a lithium secondary battery according to claim 1 . 15 . A lithium secondary battery comprising the anode of the lithium secondary battery according to claim 14 .

16. A vehicle comprising the lithium secondary battery according to claim 15.

Citation Information

Patent Citations

  • Electronic device including wireless earphone and cradle, and method of operating the same

    KR1020230106486A